Crossing the Euro rubicon [information systems]. - Grothenhuis, K.
Readying information systems for the Euro, though technically no big deal, is a massive undertaking a company should begin sooner rather than later. The Euro will directly affect 370 million inhabitants that produce 27 percent of the worlds gross national product. Its impact will be greatest on banks and financial institutions, but the change will affect virtually every European business as well as any US businesses that have subsidiaries in, trade with, or invest in Europe. Companies affected will need to reevaluate every aspect of their business that involves money, including accounting procedures, legal and taxation issues, procurement, sales, and payroll
Keywords: Euro; European business; Accounting procedures; Banks; Financial institutions; Information systems; Legal issues; Payroll; Procurement; Sales; Single European currency; Taxation issues